Determining the effects of biochar and an arbuscular mycorrhizal inoculant on the growth of fowl mannagrass (Glyceria striata) (Poaceae) - Sadie Moland; Brent M. Robicheau; Robin Browne; Ruth Newell; Allison K. Walker (Canadian Science Publishing, 2018)
Biochar is gaining attention as an organic soil amendment that can increase plant yields and improve soil fertility. We studied the effect of biochar on the growth of fowl mannagrass (Glyceria striata (Lam.) Hitchc.) (Poaceae), propagated in a greenhouse for future re-introduction into restored wetlands. Three different application rates (10%, 50%, and 75% biochar volume/substrate volume (v/v)) of nutrient-charged (i.e., nutrients added) and uncharged biochar were tested with and without a commercial arbuscular mycorrhizal fungal (AMF) inoculant. Aboveground biomass (shoot mass), belowground biomass (root mass), and shoot height of 166 G. striata samples were recorded after 92 d of growth. Using generalized linear models our data indicated a 50% (v/v) application rate of nutrient-charged biochar without AMF produces a significantly greater growth response (4.4× greater shoot height and 85× greater shoot mass compared with 0% biochar (AMF negative) control). We propose that the increased G. striata growth may be due to changes in pH, and (or) increased nutrient availability due to the addition of biochar. We recommend an application rate of 50% biochar (v/v) charged with nutrients as an advantageous amendment for propagating G. striata.